Assessment of the Relationship between Nurses’ Perception of Ethical Climate and Job Burnout in Intensive Care Units - Rivaz, Mozhgan; Asadi, Fatemeh; Mansouri, Parisa (Investigación y Educación en Enfermería, 2020)
Objective. To determine the relationship between ethical climate and burnout in nurses working in Intensive Care Units (ICUs). Methods. This cross-sectional and multi-center study was conducted among 212 nurses working in adult ICUs of six hospitals affiliated to Shiraz University of Medical Sciences, Iran in 2019. The participants were selected using systematic random sampling technique. Data was collected using valid instruments of Olson’s Hospital Ethical Climate Survey (HECS) and Maslach Burnout Inventory (MBI). Results. Ethical climate was favorable (3.5±0.6). The intensity (32.2±12.4) and frequency (25.5±12.4) of burnout were high. Ethical climate had significant and inverse relationships with frequency of burnout (r =-0.23, p=0.001) and with intensity of burnout (r=-0.186, p=0.007). Ethical climate explained 5.9% of burnout. Statistically significant relationships were also found between these factors: age with ethical climate (p=0.001), work shifts with burnout (p=0.02), and gender and with intensity frequency of burnout in ICU nurses (p=0.038). The results of Spearman correlation coefficient showed significant and inverse relationships between ethical climate and job burnout (r=-0.243, p<0.001). Conclusion. Nurses in ICUs perceived that ethical climate was favorable however, burnout was high. Therefore, burnout can be affected by many factors and it is necessary to support ICU nurses since they undertake difficult and complicated task. It is recommended to assess factors that increase burnout and adopt specific measures and approaches to relieve nursing burnout.